The Influence of Customer Perceived Value toward Customer Satisfaction in Jababeka Golf & Country Club - Ihsan Hadiansah (President University, 2017)
This study was look into the factors that influence customer satisfaction in Jababeka Golf & Country Club. It is important to find out the factors that influence consumer Satisfaction. In this study, the researcher used questionnaires with Likert scales and 452 samples as quantitative method and STATISTICAL SOFTWARE v16.0 to analyze the collected data. The research set up 3 independent variables that might influence consumer Satisfaction toward Jababeka Golf & Country Club. From the outcome of research, the researcher found out among the three variables that are functional value, emotional value, and social value. Functional value, emotional value, and social value has significant influence consumer Satisfaction toward Jababeka Golf & Country Club. Functional value is the dominant factor that has the deepest impact toward Jababeka Golf & Country Club